Crushing behavior of cone-cylinder-cone composite system - Mahdi, E.; Hamouda, A. M. S.; Sahari, B. B.; Khalid, Y. A. (Taylor and Francis Group, 2002)
This article examines the effect of cylindrical part length on the crushing behavior, energy absorption, failure mechanism, and failure mode of cone-cylinder-cone intersection composite shell. The static crushing behavior of a cone-cylinder-cone composite shell under uniform axial compressive load has been investigated experimentally and numerically. The conical parts of the structure were symmetric. The cone vertex angles used were 10° and 15°. The cylindrical part lengths were varied between 0 and 50 mm. Failure modes were examined using photographs taken while crushing the specimens. Numerical results show that local stress has been concentrated at the junctions between the cylinder and cones. Experimental results show that the initial failure was dominated by interfacial and shear failure, while the delamination and eventually fiber fracture dominated the failure mechanism after the initial failure. The results showed also that structure with Hz2/H Z ratios between 0.06 and 0.11 exhibit high-energy absorption capability and very high crushing load. Volume reduction was obtained and found to be significant.